2022
DOI: 10.1186/s40001-022-00833-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of intractable diseases using nanoparticles to interfere with vascular supply and angiogenic process

Abstract: Angiogenesis is a vital biological process involving blood vessels forming from pre-existing vascular systems. This process contributes to various physiological activities, including embryonic development, hair growth, ovulation, menstruation, and the repair and regeneration of damaged tissue. On the other hand, it is essential in treating a wide range of pathological diseases, such as cardiovascular and ischemic diseases, rheumatoid arthritis, malignancies, ophthalmic and retinal diseases, and other chronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 332 publications
(326 reference statements)
0
5
0
Order By: Relevance
“…Also, low breaking strength has been found in diabetic animal models leading to hampered angiogenesis . Delayed healing and persistent wounds have been linked to impaired angiogenesis …”
Section: Challenges In Diabetic Wound Healingmentioning
confidence: 99%
“…Also, low breaking strength has been found in diabetic animal models leading to hampered angiogenesis . Delayed healing and persistent wounds have been linked to impaired angiogenesis …”
Section: Challenges In Diabetic Wound Healingmentioning
confidence: 99%
“…1. Novel therapeutic strategies have been designed to optimize efficacy, minimize adverse events, and minimize the frequency of interventions [32,33]. Because VEGF and its receptor, VEGFR, play key roles in the pathogenesis of CNV and RVO [34][35][36][37].…”
Section: Fundus Neovascular Diseases and Their Treatmentmentioning
confidence: 99%
“…Recent research has shown that there is potential for MXene to be used in diagnostic nanomedicine, image processing, biosensing, as an antibacterial agent, and in the treatment of cancer . MXenes have been described as multipurpose theragnostic agents for effective magnetic resonance (MR) and photoacoustic (PA) dual-modality imaging-guided photothermal treatment (PTT) against cancer because of their great biocompatibility, which is a crucial route. , This is possible because of the MXenes’ ability to inhibit the formation of reactive oxygen species. MXenes make it easier to manufacture mediator-free biosensors by allowing for direct electron transfer between the bioreceptors and the electrode and by functioning as biomolecule immobilization frameworks to preserve active proteins.…”
Section: Biocompatibilitymentioning
confidence: 99%